2022
DOI: 10.34019/1982-8047.2022.v48.36065
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de medicamentos potencialmente inapropriados e da polifarmácia em pacientes idosos em um hospital universitário

Abstract: Introdução: O Brasil, assim como outros países, vem alterando seu perfil demográfico elevando o número de pessoas idosas, o que repercute em mudanças não só para sociedade, mas também para saúde pública. Este grupo de pacientes é mais vulnerável devido à fisiologia inerente ao envelhecimento, logo se tornam mais propensos ao uso de medicamentos que podem causar outros problemas de saúde. Essa probabilidade de risco é uma preocupação atual e levou a criação de métodos que norteiam os prescritores para adequarem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…In a retrospective chart analysis study (n=406) of older adults receiving care in the secondary care setting of a Reference Center for Elderly Health Care, it was found that 66.8% of participants had at least one PIM in the presence of polypharmacy 20 . According to Neves et al 9 , who assessed individuals above 60 years old hospitalized (n=187), a similar percentage of 66.7% of participants with polypharmacy and PIM was observed. In both studies, the drug omeprazole was among the most prevalent.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a retrospective chart analysis study (n=406) of older adults receiving care in the secondary care setting of a Reference Center for Elderly Health Care, it was found that 66.8% of participants had at least one PIM in the presence of polypharmacy 20 . According to Neves et al 9 , who assessed individuals above 60 years old hospitalized (n=187), a similar percentage of 66.7% of participants with polypharmacy and PIM was observed. In both studies, the drug omeprazole was among the most prevalent.…”
Section: Discussionmentioning
confidence: 62%
“…Central nervous system-acting cholinergic antidepressants are considered inappropriate due to their sedative effects, which increase the risk of falls and fractures in patients1. Benzodiazepines that act on the central nervous system have anxiolytic and anticonvulsant effects, and although suggested for anxiety and insomnia disorders-common issues faced by older adults-they may enhance the risks of falls, cognitive deficits, delirium, fractures, and further exacerbate the effects of depression 8,9,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em um estudo retrospectivo de análise de prontuários (n=406) de pessoas idosas atendidas na atenção secundária de um Centro de Referência em Atenção à Saúde da Pessoa Idosa, foi encontrado que 66,8% dos participantes apresentavam pelo menos 1 MPI quando na presença de polifarmácia 20 . De acordo com Neves et al 9 que avaliaram pessoas acima de 60 anos que estavam hospitalizadas (n=187) também foi encontrado a porcentagem aproximada de 66,7% de participantes com polifarmácia e MPI. Em ambos os estudos, o fármaco omeprazol foi um dos mais prevalentes.…”
Section: Discussionunclassified
“…Os MPI são definidos como fármacos em que a probabilidade de causar efeitos adversos é maior que a de benefícios para a saúde. Se utilizado de forma prolongada e em excesso podem ocasionar interações farmacológicas, trazendo prejuízos para a saúde como: disfunções físicas, intoxicações 6 , hospitalizações 7 , demência 8 , insuficiência renal 9 e a fragilidade da pessoa idosa 10 .…”
Section: Introductionunclassified